Social Support and Its Impact on Job Satisfaction and Emotional Exhaustion - Pablo Garmendia; Samuel Fernández-Salinero; Ana Isabel Holgueras González; Gabriela Topa (MDPI AG, 2023)
Social support at work has demonstrated itself to be an important variable for predicting desirable outcomes and helping to buffer the effects of adverse events. The main objective of this research is to understand the impact of social support on job satisfaction on the one hand and emotional exhaustion on the other. Furthermore, in order to gain a deeper understanding of intricate organizational relationships, the mediating effects of work recovery experiences are taken into consideration. The sample was composed of 496 workers (41.5% men and 58.5% women). The mean age was 42 years (SD = 9.82). A cross-sectional design was used. The results, both direct (r = 0.43; R2 = 0.19; p < 0.001) and indirect (B = 0.04; SE = 0.02; 95% C.I. = 0.01, 0.09), of the model relating social support to job satisfaction were statistically significant. On the other hand, in the model that links social support to emotional exhaustion, we observed statistically significant direct (r = 0.26; R2 = 0.07; p < 0.001) and indirect effects (B = −0.05; SE = 0.02; 95% C.I. = −0.10, −0.01). Only the relaxation factor was a significant mediator of these variables. Implications, limitations, and future research recommendations are discussed.